The Prognostic Value of (18)F-FDG PET/CT for Early Recurrence in Operable Breast Cancer: Comparison with TNM Stage - O, Joo Hyun (Springer Berlin Heidelberg, 2013)
PURPOSE: We evaluated whether the maximum standardized uptake values (SUV(max)) of primary tumor from the initial staging by (18)F-fluorodeoxyglucose positron emission tomography/computed tomography ((18)F-FDG PET/CT) of patients with breast cancer could identify patients at risk for early recurrence within 2 years, particularly in comparison to the American Joint Committee on Cancer (AJCC) stage. METHODS: We reviewed the staging (18)F-FDG PET/CT images of patients with primary breast cancer and their medical records. The SUV(max) of the primary tumor was measured. The presence or absence of FDG uptake in the axillary lymph node (ALN) was also assessed. The patient’s pathologic primary tumor stage (pT), pathologic regional lymph node stage (pN), stage grouping, age, estrogen receptor (ER) and progesterone receptor (PR) status, and neoadjuvant chemotherapy history were evaluated with the FDG uptake parameters for recurrence within 2 years following the end of first-line therapy. RESULTS: Recurrence within 2 years was present in 9.1 % (n = 40) out of the 441 patients assessed. The FDG uptake in ALN, pT, pN, stage grouping and neoadjuvant chemotherapy history were prognostic for early recurrence, while primary tumor SUV(max), age, and ER or PR status were not significant on logistic regression. On multivariate analysis, only the stage grouping (odds ratio 2.79; 95 % CI 1.73, 4.48; p < 0.0001) and neoadjuvant chemotherapy history (odds ratio 2.70; 95 % CI 1.22, 5.98; p = 0.0141) could identify patients at increased risk for recurrence within 2 years. CONCLUSIONS: Primary tumor FDG uptake measured by SUV(max), and visual assessment of FDG uptake in the ALN in the initial staging PET/CT of patients with breast cancer may not have additional prognostic value compared with the AJCC stage grouping for early recurrence.